Evaluation of response after neoadjuvant treatment in soft tissue sarcomas; the European Organization for Research and Treatment of Cancer–Soft Tissue and Bone Sarcoma Group (EORTC–STBSG) recommendations for pathological examination and reporting. (January 2016) - Wardelmann, E.; Haas, R.L.; Bovée, J.V.M.G.; Terrier, Ph; Lazar, A.; Messiou, C.; LePechoux, C.; Hartmann, W.; Collin, F.; Fisher, C.; Mechtersheimer, G.; DeiTos, A.P.; et al.
Abstract: At present, there is not a commonly used and generally accepted standardized approach for the pathologic evaluation of pretreated soft tissue sarcomas. Also, it is still unclear whether the cut-off for prognostic relevance is similar in the many different histological subtypes of STS. This manuscript, produced by a European Organization for Research and Treatment of Cancer – Soft Tissue and Bone Sarcoma Group (EORTC–STBSG) endorsed task force, aims to propose standardization of the pathological examination process and the reporting of STS resection specimens after neoadjuvant radio- and/or chemotherapy. Highlights: At present, no standardized pathologic evaluation criteria of soft tissue sarcomas (STS) exist. Also, it is unclear whether the cut-off for prognostic relevance is similar among STS subtypes. Here, the EORTC–STBSG proposes a standardization of the pathological examination process. This manuscript focuses on reporting of STS resection specimens after neoadjuvant therapy.